2011
DOI: 10.1523/jneurosci.4152-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β/Fyn–Induced Synaptic, Network, and Cognitive Impairments Depend on Tau Levels in Multiple Mouse Models of Alzheimer's Disease

Abstract: Alzheimer’s disease (AD), the most common neurodegenerative disorder, is a growing public health problem and still lacks effective treatments. Recent evidence suggests that microtubule-associated protein tau may mediate amyloid-β peptide (Aβ) toxicity by modulating the tyrosine kinase Fyn.Weshowed previously that tau reduction prevents, and Fyn overexpression exacerbates, cognitive deficits in human amyloid precursor protein (hAPP) transgenic mice overexpressing Aβ. However, the mechanisms by which Aβ, tau, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
633
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 588 publications
(683 citation statements)
references
References 71 publications
36
633
3
3
Order By: Relevance
“…6B and C). Similarly, ablation of the microtubule‐associated protein tau, which has been shown to reduce epileptic activity in a variety of seizure models,28, 30, 31, 32, 33, 34 tended to reduce interictal events by roughly 50% but, if anything, tended to slightly increase the left shift in spectral power in SYN mice (Fig. 6D and E).…”
Section: Resultsmentioning
confidence: 76%
“…6B and C). Similarly, ablation of the microtubule‐associated protein tau, which has been shown to reduce epileptic activity in a variety of seizure models,28, 30, 31, 32, 33, 34 tended to reduce interictal events by roughly 50% but, if anything, tended to slightly increase the left shift in spectral power in SYN mice (Fig. 6D and E).…”
Section: Resultsmentioning
confidence: 76%
“…We therefore crossed hTau‐A152T (L1) mice and hTau‐WT (L32) mice with hAPP transgenic mice from line J20 (hAPP‐J20) (Fig 11A–D). hAPP‐J20 mice have pathologically elevated levels of human Aβ in the brain, increased risk of early death (most likely from epileptic activity), and AD‐like features, including memory problems, behavioral alterations, synaptic impairments, amyloid plaques, neuritic dystrophy, astrocytosis, and microgliosis 49, 50, 51, 52, 53.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the survival of mice coexpressing hAPP/Aβ and hTau‐A152T, we crossed hTau‐A152T (L1) mice with mice from hAPP line J9 (hAPP‐J9), which express hAPP/Aβ at lower levels than hAPP‐J20 mice 50, 54, 55, 56. Among 282 offspring from crosses of hTau‐A152T (L1) and hAPP‐J9 mice, only eight were triply transgenic (Fig 11E).…”
Section: Resultsmentioning
confidence: 99%
“…While our work provides evidence that tau knockdown impairs learning and memory in wild‐type mice, a vast number of studies have shown that knockout of endogenous tau in AD mouse models protects against Aβ‐induced cognitive deficits (Ittner et al., 2010; Ke et al., 2012; Roberson et al., 2011; Vossel et al., 2015). For example, crossing APP mice with tau knockout mice improved spatial reference memory (Roberson et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, crossing APP mice with tau knockout mice improved spatial reference memory (Roberson et al., 2011). Mechanistically, these changes were linked to a reduced susceptibility to excitotoxicity in APP mice lacking the tau gene.…”
Section: Discussionmentioning
confidence: 99%